Effect of skin-to-skin contact at birth on early neonatal hospitalization. (May 2020) - Agudelo, Sergio; Díaz, Diana; Maldonado, María José; Acuña, Eduardo; Mainero, Daniel; Pérez, Oman; Pérez, Laura; Molina, Carlos
Abstract: Background: Skin-to-skin contact (SCC) at birth has a positive impact on breastfeeding indicators and physiological stabilization at birth. On the other hand, globally and in Colombia, morbidity and mortality have increased in intermediate- and low-risk infants. The aim of the study was to assess the effect of immediate skin-to-skin contact, compared to separation at birth, on the risk of hospitalization of intermediate- and low-risk infants prior to discharge from the maternity ward. Methodology: A retrospective cohort study of newborn who underwent a SCC compared to habitual management was conducted. Intermediate- and low-risk neonates with spontaneous neonatal adaptation and cardiorespiratory stability at birth were included. Main outcome measure was hospital admission prior to the discharge from the maternity ward. Result: A total of 816 infants were included, 672 (82.3%) in the skin-to-skin contact group and 144 (17.6%) in the habitual management group. The main causes of hospital admission were jaundice and feeding/sucking related issues. Significantly lower admission to the neonatal unit was found for infants in the contact group compared to infants who did not receive skin-to-skin contact (13.8% vs. 26.4%; OR 0.46, 95% CI 0.29–0.71, p  = 0.001). Conclusion: Skin-to-skin contact in newborns of intermediate and low risk has protective effects on the risk of hospital admission within the first few hours of life. SSC is proposed as a prevention strategy in second-level care scenarios. Highlights: Skin-to-skin contact, in newborns, decrease the hospital admission before discharge of maternity ward. Skin-to-skin contact is a prevention strategy in second-level care scenarios, improving the health of the newborn. The Skin-to-skin contact could have a protective effect on early morbidity.